FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STBM PILAR 1 (BUANG AIR BESAR SEMBARANGAN) PADA MASYARAKAT - Cut Juliana; Syahril Syahril; Salfani Oktaniara (Universitas Pahlawan, 2022)
Stop Open Defecation Fee (ODF) is one of the activities in the Community Led Total Sanitation Program. The Community Led Total Sanitation (CLTS) is an approach to change hygienic and sanitary behavior through community empowerment by triggering. However, for the implementation of the program, out of 23 regencies/cities in Aceh Province, there is only one area that has implemented a Stop ODF, that is Banda Aceh City. Meanwhile, other areas still exhibit open defecation fee behavior, including Bener Meriah Regency. This study was carried out with the aim of knowing the relationship between knowledge, family income, the role of health workers and ownership of latrines with open defecation fee in the community in Nosar Tawar Jaya Village, Bener Kelipah District, Bener Meriah Regency. This study uses an analytical survey method with a cross sectional approach to 70 respondents. Then the data were analyzed using chi-square statistics. The results of the bivariate analysis showed that from 70 respondents, it was found that there was a relationship between knowledge (P 0.000), family income (P 0.004), the role of health workers (P 0.004) and latrine ownership (P 0.000) with open defecation fee. The suggestion is, it is hoped that the community will maintain personal, family, and environmental hygiene by stopping open defecation to prevent diseases caused by the environment. Furthermore, to the relevant agencies in order to carry out the maximum socialization related to the Community Led Total Sanitation Program. Keywords : Open Defecation Fee, Knowledge, Family Income, role of health workers and latrine ownership, Community Led Total Sanitation.